Modulation of hepatotoxicity, DNA fragmentation and gene expression of Solanum nigrum leaves extract in rats treated with silver nanoparticles - Mosaad A. Abdel-Wahhab, Helmy M.S. Ahmed, Sekena H. Abdel-Aziem, Aziza A. El-Nekeety, Heba A.M. Abd El-Kader, Mohamed S. Abdel-Aziz, Mohamed A. Hamazawy, Hafiza A. Sharaf, Hadeer M. Naguib, Ezzeldeen S. El-Denshary (Journal of Applied Pharmaceutical Science, 2017)
The current study aimed to determine the antioxidant compounds in Solanum nigrum (S. nigrum) leaves extract, to synthesize silver nanoparticles (AgNPs) and to evaluate the protective role of the extract against the hepatotoxicity and genotoxicity of AgNPs compared to CCl4 in rats. Eight groups of female Sprague-Dawley rats were treated orally for 3 weeks included the control group, CCl4-trared group (0.1 ml/kg b.w twice a week), AgNPs-treated group (50 mg/kg b.w/day), AgNPs plus CCl4-treated group, S. nigrum leaves extract-treated group (0.5 mg/kg b.w) and the groups treated with AgNPs and/or CCl4 plus the extract. The results indicated that the extract was rich in the total phenolic, flavoniods and β-carotene. The size of synthesized AgNPs was 30-50 nm. Administration of AgNPs and/or CCl4 resulted in severe hepatotoxicity and histological changes, increased DNA fragmentation and down regulation of antioxidant gene expression in liver. The extract was safe and succeeded to mitigate the hazards effect of AgNPs and/or CCl4. It could be concluded that AgNPs have toxic effects and caution should be taken when they use in food or medical application. S. nigrum extract succeeded to protect the liver due to its higher content of antioxidant compounds.
Keywords: Silver nanoparticles, Solanum nigrum, Liver,DNA fragmentation,gene expression.